Assessment of concentration and distribution of heavy metals in water-sediment facies in Langat River, Malaysia - Lim, Wan Ying (2013)
The release of pollutants such as heavy metals into aquatic environment attributed to dense development bears a direct effect to river ecosystem and becomes an emerging issue nowadays. This thesis discusses the heavy metals variation and their pollution magnitude status in Langat River, based on heavy metal concentrations, comparison with different standard guidelines, application of different indices and indicator,statistical and modelling analyses. In general, this study aimed to provide data on the spatial and temporal variation of heavy metals in river water and sediment, their potential pollution sources and ecological risk area. The metal speciation and saturation indices based on PHREEQC modelling was also presented. A total of 30 sampling stations (LY 1 to LY 30) were selected and the samplings were conducted during the wet (December 2010) and dry (July 2011) seasons. Triplicate of water and sediment samples were collected simultaneously and subjected to analyses. Both water and sediment samples were analyzed for heavy metals concentration (aluminium (Al), arsenic (As), barium (Ba), cadmium (Cd), cobalt (Co), copper (Cu), chromium (Cr), iron (Fe), manganese (Mn), nickel (Ni), lead (Pb), and zinc (Zn)) using an Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Based on measurement, each metals were found varied significantly among sampling stations and seasons (p<0.05). In general, the concentration levels of heavy metals were more likely to be high in wet season and this statement was supported by the calculation of degree of contamination. Most of the water samples were within the drinking water quality standards stipulated by the World Health Organization (WHO) and the Malaysia Ministry of Health (MOH), except for Al, As, Fe, Ni and Mn at certain sampling stations. For sediment samples, most of the studied metals did not exceed the Interim Sediment Quality Guidelines (ISQG-high values), except for As and Pb. Based on the environmental forensic investigation via the use of analytical analyses, water and sediment quality standards,different indicators and geochemical indices, as well as multivariate analyses, it can be summarized that the pollution sources responsible for both sediment and water are anthropogenic (agricultural and industrial activities) and natural (seawater intrusion and geological weathering) processes. In addition, the significant relationships between certain parameters (pH, Eh, salinity, and CEC) with metals identified the intrinsic factors contributing to the mobility of metal in Langat River and their tendency to depict a similar trend of distribution pattern. The hierarchical cluster analysis (HCA) renders the sampling stations into two clusters for both wet and dry seasons. Both seasons yield a similar cluster where Cluster 1 (LY 15 to LY 30) was mainly influenced by the agricultural and industrial pollution while Cluster 2 (LY 1 to LY 14) was affected by seawater. Meanwhile, the mineral saturation indices and the distribution of aqueous species in river water were performed using hydrochemical model, PHREEQC. Heavy metals were divided into three groups: (i) Ba2+, Mn2+, Zn2+, and Cu2+ which dominated by free ions; (ii) Fe3+ and Al3+ which dominated by hydroxyl species; (iii) Cd2+ and Pb2+ which dominant by sulfate and chloride species. The saturation indices revealed that the samples were mostly under-saturation or close to saturation with respect to analyzed minerals, except gibbsite, goethite, and hematite. Thus, this study recommends an environmental forensics research approach to illustrate the degree of metal pollution in the Langat River as well as the origin of these metals. The outcomes of this approach provide a better understanding on the pollution magnitude, evaluation of potential ecological risks and contamination status of the river.